2015
DOI: 10.1021/acs.analchem.5b00725
|View full text |Cite
|
Sign up to set email alerts
|

Digital Microfluidic Approach for Efficient Electroporation with High Productivity: Transgene Expression of Microalgae without Cell Wall Removal

Abstract: A unique digital microfluidic electroporation (EP) system successfully demonstrates higher transgene expression than that of conventional techniques, in addition to reliable productivity and feasible integrated processes. By systematic investigations into the effects of the droplet EP conditions for a wild-type microalgae, 1 order of magnitude higher transgene expression is accomplished without cell wall removal over the conventional bulk EP system. In addition, the newly proposed droplet EP method by a drople… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 58 publications
(94 reference statements)
0
43
0
Order By: Relevance
“…Because common polymeric materials applied in rapid prototyping of microfluidic channels cannot withstand the harsh pressure, temperature, and solvents applied in conventional physical, mechanical, and chemical treatments, electroporation becomes a convenient and favorable process to weaken the cell outer compartments. Starting from 2010, microfluidic electroporation has been applied on the aqueous extraction [79], gene transfection [80, 81], and molecule delivery [82, 83] for microalgae. Owing to the closely arranged electrodes in microfluidic systems, extremely low voltage (1 V–50 V) can be used to generate an electric field larger than thousands of voltage per centimeter.…”
Section: Downstream Treatmentsmentioning
confidence: 99%
“…Because common polymeric materials applied in rapid prototyping of microfluidic channels cannot withstand the harsh pressure, temperature, and solvents applied in conventional physical, mechanical, and chemical treatments, electroporation becomes a convenient and favorable process to weaken the cell outer compartments. Starting from 2010, microfluidic electroporation has been applied on the aqueous extraction [79], gene transfection [80, 81], and molecule delivery [82, 83] for microalgae. Owing to the closely arranged electrodes in microfluidic systems, extremely low voltage (1 V–50 V) can be used to generate an electric field larger than thousands of voltage per centimeter.…”
Section: Downstream Treatmentsmentioning
confidence: 99%
“…Another technique directly interfaced pin headers with a microfluidic chamber to improve the controllability of and ease of electroporation. 50 A standard micropipette was used to deliver 1 to 2 μL mixtures of DNA and cells. This system successfully delivered genes to microalgae 50 and Jurkat T cells 56 with efficiencies of ∼6× and ∼10×, respectively, higher than their conventional counterparts.…”
Section: Transformation/transfection Of Cellsmentioning
confidence: 99%
“…50 A standard micropipette was used to deliver 1 to 2 μL mixtures of DNA and cells. This system successfully delivered genes to microalgae 50 and Jurkat T cells 56 with efficiencies of ∼6× and ∼10×, respectively, higher than their conventional counterparts. The authors credited these improvements due to the decreased electric current afforded by the smaller reaction volume.…”
Section: Transformation/transfection Of Cellsmentioning
confidence: 99%
“…The application of electrostatic actuation of water droplets in dielectric oil has also been investigated. Im et al reported electrophoretic actuation of water-in-oil droplets containing living cells [27], and also successfully investigated gene transfection of microalgae [28][29][30] and Jurkat cells [31] using their droplet-based system.…”
Section: Introductionmentioning
confidence: 99%